ANALYSIS OF FACTORS OF MATERNAL MORTALITY RATE IN MEDAN CITY USING BIVARIAT POISSON REGRESSION - Sirait, Anita Ningsih; Fairuz, Ersya Nurul; Nikmah, Khairun; Sembiring, Tesya Yunita (Journal of Mathematics and Scientific Computing With Applications, 2022)
There are several factors that cause maternal death, such as bleeding, hypertension, infection, prolonged labor, abortion and others. Maternal deaths related to pregnancy, childbirth and the puerperium (42 days after delivery), and the number of deaths per 100,000 live births related to pregnancy or medical problems (except accidents or incidents). In this study the case of maternal mortality using the Bivariate Poisson Regression model which aims to determine what factors are the main factors in maternal mortality using the Bivariate Poisson regression method.